2007
DOI: 10.1186/1471-2458-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Can current national surveillance systems in England and Wales monitor sexual transmission of hepatitis C among HIV-infected men who have sex with men?

Abstract: BackgroundRecent reports suggest an increase in sexually-transmitted hepatitis C infection among HIV-infected men who have sex with men (MSM) in European cities. We investigated whether current national surveillance systems in England and Wales (E&W) are able to monitor sexual transmission of hepatitis C infection among HIV-infected MSM.MethodsRoutine laboratory reports of hepatitis C diagnoses and data from sentinel hepatitis C testing surveillance were matched to HIV diagnosis reports to determine: (i) the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 12 publications
1
29
0
1
Order By: Relevance
“…Following reports of emergence of acute HCV in HIV-positive MSM, many have called for routine screening and targeted prevention in this group 1 2 6–8 29 30 . w1 w2 Reports of increased HCV incidence among HIV-negative MSM have also prompted some to argue that acute HCV is an expanding epidemic among all MSM and that universal screening in the MSM population should be undertaken 29 30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following reports of emergence of acute HCV in HIV-positive MSM, many have called for routine screening and targeted prevention in this group 1 2 6–8 29 30 . w1 w2 Reports of increased HCV incidence among HIV-negative MSM have also prompted some to argue that acute HCV is an expanding epidemic among all MSM and that universal screening in the MSM population should be undertaken 29 30 .…”
Section: Introductionmentioning
confidence: 99%
“…w1 w2 Reports of increased HCV incidence among HIV-negative MSM have also prompted some to argue that acute HCV is an expanding epidemic among all MSM and that universal screening in the MSM population should be undertaken 29 30 . w1–w3 A number of these calls, however, were supported not by studies describing incidence of acute HCV, but by case studies wherein traumatic sexual behaviour was the only known or significant risk factor for infection 1 2 30 . w2 Furthermore, recent cross-sectional studies have found a low prevalence of HCV in HIV-positive MSM without a history of injection drug use.…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom there are several shortcomings in the current national surveillance systems for HCV 14 – 15. Risk factors are poorly recorded (less than a third of the laboratory reports contain this information) and reports are often incomplete, particularly in London 16.…”
mentioning
confidence: 99%
“…This would enable automated collection of large amounts of data without additional work by the person requesting the test or the need for labour-intensive local audits. It would also provide the opportunity to monitor testing for co-infection with hepatitis B and C in HIV-positive individuals, something which is not currently possible with existing surveillance systems 15. Such a scheme may also be of value in other countries, particularly those with national healthcare systems where data collection from a network of representative sentinel laboratories is feasible.…”
Section: Discussionmentioning
confidence: 99%